2013
DOI: 10.1177/0143831x13491616
|View full text |Cite
|
Sign up to set email alerts
|

Scandinavian welfare states and gender (de) segregation: Recent trends and processes

Abstract: High levels of gender segregation in Scandinavian labour markets have been referred to as a paradox in view of these countries’ commitment to gender equality and advancements in other areas. The status of gender segregation in these welfare states is addressed here: Are they (still) the most gender segregated? What processes drive (de)segregation? Relatively fast occupational desegregation in recent years has moved Denmark, Norway and Sweden from the group of highly to moderately gender segregated labour marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 31 publications
3
35
0
5
Order By: Relevance
“…Others argue that what seems like a paradox is not as paradoxical as one might think, and that the main reason why some countries seem to have less gender segregated labour markets is that a large share of the female typed (care) work is being carried out outside the labour market (Reisel & Teigen, 2014c). In fact, several cross-national studies have found that high female labour market participation rates explain the comparatively high levels of gender segregation in otherwise more gender equal countries, like the Nordic countries (Barth, Hardoy, Schøne , & Østbakken, 2014;Ellingsaeter, 2013;Korpi, Ferrarini, & Englund, 2013;Nermo, 2000).…”
Section: Comparative Studiesmentioning
confidence: 99%
“…Others argue that what seems like a paradox is not as paradoxical as one might think, and that the main reason why some countries seem to have less gender segregated labour markets is that a large share of the female typed (care) work is being carried out outside the labour market (Reisel & Teigen, 2014c). In fact, several cross-national studies have found that high female labour market participation rates explain the comparatively high levels of gender segregation in otherwise more gender equal countries, like the Nordic countries (Barth, Hardoy, Schøne , & Østbakken, 2014;Ellingsaeter, 2013;Korpi, Ferrarini, & Englund, 2013;Nermo, 2000).…”
Section: Comparative Studiesmentioning
confidence: 99%
“…Sickness absence may be regarded as more legitimate in a ‘working class culture’ 34. Working class occupations are also more gender segregated,35 and female-dominated workplaces have somewhat higher levels of sickness absence in Norway, possibly because of gender-specific norms 36. Working-class women are more likely to express family-oriented values, while middle-class women more often are characterised by occupational dedication 37.…”
Section: Background and Significancementioning
confidence: 99%
“…This is particularly prominent in foreign subsidiaries stemming from countries with higher gender equality, such as the Scandinavian countries, which operate in host countries with lower gender diversity and equality such as Japan. Scandinavian countries have a good reputation in terms of gender diversity and equality, as beside a high share of women in the workforce and managerial ranks, they are also characterized by a low gender wage gap (Ellingsaeter, 2013). In Japan, in turn, gender segregation is still very common and Japan is characterized by a rather low representation of women in managerial ranks, a high gender wage gap, and a low return rate after maternity (Kemper, Bader, & Froese, 2016;Nemoto, 2013b;The Economist, 2017).…”
Section: Introductionmentioning
confidence: 99%